Predictors of Future Walking Speed: A 12-Month Monitoring Program. (September 2022) - Dunsky, Ayelet; Zeev, Aviva; Netz, Yael
The purpose of the current study was to identify significant predictors of walking speed (WS) among community-dwelling older adults, as it is one of the most representative measures of functioning in their daily lives. Seventy-seven (24 adult men, 26 adult women, and 27 older-adult women) community-dwelling older adults (73.7 ± 4.9 years) performed two assessments, over a 12-month period. Several physical, cognitive, and psychological tests were performed, as well as assessing the preferred WS. Multiple linear regression, stratified by gender, was used to identify significant predictors of future WS. For the adult men, walking and functional performances at the first assessment predicted 71.9%; for adult women, reaction time, walking, and balance performance predicted 64.4%; and, for the older-adult women, fast walking and reaction time predicted 48.2% of the variance of future WS. Clinicians should consider including different exercises for each group of older adults to evaluate and preserve functional abilities.